2022
DOI: 10.4239/wjd.v13.i10.851
|View full text |Cite
|
Sign up to set email alerts
|

Advances in traditional Chinese medicine as adjuvant therapy for diabetic foot

Abstract: Diabetes mellitus (DM) is a complex disease that often causes multiple systemic complications that have become a major international public health problem. Diabetic foot (DF) is one of the severe and frequent chronic complications of DM due to vascular lesions and neuropathy. DF ulcers (DFU) affect approximately 15% of people with DM and are the leading cause of death and disability. The prevalence and recurrence of DF are worrisome, and morbidity and mortality are also on the rise, which poses a substantial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…[ 12 ] Impaired microvascular reactivity diminishes the blood supply to ulcerated areas, [ 13 ] and insufficient vascularization, tissue hypoxia, and a high probability of infection contribute to delayed wound healing. [ 7 ] For these 2 cases, case 2, especially poor glycemic control and inadequate microcirculation, led to severe DFUs. However, conventional treatments such as infection, glycemic control, and local ulcer care failed to promote ulcers healing in these 2 cases, suggesting that a sufficient supply of blood and oxygen is essential for accelerating tissue healing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 12 ] Impaired microvascular reactivity diminishes the blood supply to ulcerated areas, [ 13 ] and insufficient vascularization, tissue hypoxia, and a high probability of infection contribute to delayed wound healing. [ 7 ] For these 2 cases, case 2, especially poor glycemic control and inadequate microcirculation, led to severe DFUs. However, conventional treatments such as infection, glycemic control, and local ulcer care failed to promote ulcers healing in these 2 cases, suggesting that a sufficient supply of blood and oxygen is essential for accelerating tissue healing.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Adjunctive therapies for DFUs such as acupuncture, massage, and acupoint injection have shown positive effects. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tis treatment method fumigates the local skin directly through the drug solution and is absorbed and transmitted through the skin and meridians to stimulate nerves and blood vessels, expand the blood vessels of the extremities, improve the blood circulation and local nerve conduction function, and efectively relieve the clinical symptoms of DPN such as pain, fatigue, and numbness [34]. Studies have shown that TCM fumigation can promote blood circulation, improve tissue oxygen and blood supply, repair damaged nerve cells [35], and inhibit the expression of proinfammatory factors [36] to achieve therapeutic purposes. Acupoint application therapy is to achieve the purpose of treatment through the direct efect of drug absorption in specifc sites and the indirect efect of acupuncture point stimulation to stimulate the qi [37].…”
Section: Discussionmentioning
confidence: 99%
“…These methods have been practiced worldwide, mainly as adjunctive treatments for chronic pain and diseases. 17 TCM is a common complementary therapy for KOA. Previous studies have shown that TCM is an effective treatment for relieving pain and swelling and improving knee joint function in patients with KOA.…”
Section: Introductionmentioning
confidence: 99%